Crosstalk between prognostic long noncoding RNAs and messenger RNAs as transcriptional hallmarks in gastric cancer. (6th February 2018) - Zhang, Jian; Yuan, Yujie; Wei, Zhewei; Ren, Jianwei; Hou, Xun; Yang, Dongjie; Cai, Sirong; Chen, Chuangqi; Tan, Min; Chen, George Gong; Wu, Kaiming; He, Yulong
Aim: Our study investigated the significance of the crosstalk between long noncoding RNAs (lncRNAs) and mRNAs in gastric cancer (GC).Methods: lncRNA and mRNA expression profiling data in 671 GC tumors and 77 nontumorous gastric tissues were retrieved from the gene expression omnibus database: GSE54129, GSE13911, GSE19826, GSE79973, GSE15459 and GSE66229. Differentially expressed analysis, RNA coexpression network construction, gene ontology (GO) and Kyoto encyclopedia of genes and genomes (KEGG) enrichment analyses were conducted in this study.Results: Using differentially expressed and prognostic lncRNAs or mRNAs in GC, we constructed the lncRNA–mRNA coexpression networks. This network involved with vital GO and KEGG pathways.Conclusion: Our study reveals coexpressed lncRNAs and mRNAs as transcriptional hallmarks in GC patients which provide interesting information regarding the incidence and outcome of GC.